Analisis Pengaruh Kepercayaan Nasabah Terhadap Risiko Menggunakan Layanan E-Banking - Alva Yenica Nandavita (Universitas Wahid Hasyim, 2022)
E-banking is a banking service product that utilizes the internet as a medium to channel financial data from banks to customers via mobile phones, smartphones or computers, which customers can use anytime and anywhere for 24 hours. This study aims to explain and analyze the effect of customer trust on the risk of using e-banking services for Islamic Banking students at the State Islamic College of Lampung Province. This research uses quantitative descriptive research. Meanwhile, for testing data analysis using validity test, reliability test, classical assumption test and simple linear regression test using SPSS ver.26. The results showed that there was a positive influence of customer trust on the risk of using e-banking services on Islamic Banking students at the State Islamic College of Lampung Province with a positive regression, so it can be said that customer trust (X) has an effect on the risk of using e-services. banking (Y).